Microsoft Teams for CEU and Training Delivery - Brett W. Bultemeier; Joe Gasper (EDIS)
The Microsoft Teams collaboration platform is popular among UF/IFAS faculty, researchers, Extension agents, and staff for its ease of use and utility for internal and external communication, collaboration, and meetings. The Teams webinar feature called live events can be used for a more controlled experience for large meetings, events, or CEU delivery. This new 5-page article will discuss the benefits and possible limitations of this service, specifically for offering online CEU material that meets Florida Department of Agriculture and Consumer Services (FDACS) guidelines for such trainings. Written by Brett W. Bultemeier and Joe Gasper and published by the UF/IFAS Pesticide Information Office. https://edis.ifas.ufl.edu/pi290